1990
DOI: 10.1159/000200392
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factors and the Developing and Mature Rat Small Intestine: Receptors and Biological Actions

Abstract: To determine if insulin-like growth factor-I (IGF-I) or multiplication stimulating activity (MSA, rat IGF-II) might directly influence small intestinal epithelium, we studied the distribution of IGF binding sites during development of the rat intestine. Cell membranes from suckling rat mucosa bound 2–6 times as much 125I-IGF-I and 3–5 times as much 125I-MSA as did adult membranes. Isolated villus cells from suckling and adult rats specifically bound both IGFs. IGF-I binding tended to rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
5

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 24 publications
(28 reference statements)
4
58
0
5
Order By: Relevance
“…It stimulates gut epithelial cell proliferation (Chen et al 1991, Steeb et al 1994 and increases gut weight in rats after dexamethasone treatment or partial gut resection . It may also accelerate maturation of gut permeability (McRoberts & Riley 1992) and brush border enzyme maturation in neonatal rats (Young et al 1990, Ma & Xu 1997. Consistent with these findings, we found that IGF-I infusion increased wall thickness in all regions of the gut studied.…”
Section: Discussionsupporting
confidence: 89%
“…It stimulates gut epithelial cell proliferation (Chen et al 1991, Steeb et al 1994 and increases gut weight in rats after dexamethasone treatment or partial gut resection . It may also accelerate maturation of gut permeability (McRoberts & Riley 1992) and brush border enzyme maturation in neonatal rats (Young et al 1990, Ma & Xu 1997. Consistent with these findings, we found that IGF-I infusion increased wall thickness in all regions of the gut studied.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with other studies (Young et al 1990, Heinz-Erian et al 1991, MacDonald 1999, binding capacities of IGF-IIR were consistently higher than those of IGF-IR and IR. As B max values were highest and mRNA expression values were lowest for IGF-IIR, the ratios of B max /mRNA were much higher in IGF-IIR than in IGF-IR and IR.…”
Section: Comparisons and Associations Between Mrna Levels And B Max Osupporting
confidence: 92%
“…Studies on site-specific and on postnatal variations of intestinal IGF-IR, IGF-IIR and IR have been reported in pigs, rabbits and rats (Schober et al 1990, Young et al 1990, Nowak et al 1996, Staley et al 1998. Differences in IGF and insulin receptor numbers at different intestinal sites as found in our calves have been reported in rats (Heinz-Erian et al 1991, Buts et al 1997, FernandezMoreno et al 1997 and are consistent with our previous studies in calves (Baumrucker et al 1994).…”
Section: Igf-ir Igf-iir and Ir Concentrations At The Mrna And Proteimentioning
confidence: 99%
“…In the orally lGF-I-treated rats, the jejunal brush border enzyme activities of maltase, lactase, alkaline phosphatase, and amino peptidase were increasedby 20,20, 50, and 2O%, rcspectively, over the controls (Young et al 1990). Young^-et al (1990) which is synchronized with the highest prevalence of gut-epithelium brush border IGF receptors (Young et al 1990) and rapid gut development in the suckling neonate. Therefore, it could be considered an oversight for Juskevich and Guyer (1990) to suggest that ingested IGF{ is inactive.…”
Section: Bioreactivity Of Milk and Milk Products From Growth' Hormonementioning
confidence: 86%
“…However, Young et al (1990) have shown in suckling rat pups that oral doses of IGF-I atl pg d-l for 6 d [3 orders of magnitude lower than the orally inactive limit for IGF-I stated by Juskevich and Guyer (1990) I were active in the stimulation ofjejunal brush border enzymes, but not in intestinal growth. In the orally lGF-I-treated rats, the jejunal brush border enzyme activities of maltase, lactase, alkaline phosphatase, and amino peptidase were increasedby 20,20, 50, and 2O%, rcspectively, over the controls (Young et al 1990). Young^-et al (1990) which is synchronized with the highest prevalence of gut-epithelium brush border IGF receptors (Young et al 1990) and rapid gut development in the suckling neonate.…”
Section: Bioreactivity Of Milk and Milk Products From Growth' Hormonementioning
confidence: 96%